Quantitative study of unsaturated transport of glycerol through aquaglyceroporin that has high affinity for glycerol. Issue 56 (15th September 2020) - Rodriguez, Roberto A.; Chan, Ruth; Liang, Huiyun; Chen, Liao Y.
Abstract : In addition to the single-glycerol mechanism for saturable kinetics, a second transport pathway becomes more significant at higher substrate concentrations, resulting in unsaturable transport characteristics of an aquaglyceroporin. Abstract : The structures of several aquaglyceroporins have been resolved to atomic resolution showing two or more glycerols bound inside a channel and confirming a glycerol-facilitator's affinity for its substrate glycerol. However, the kinetics data of glycerol transport experiments all point to unsaturated transport that is characteristic of low substrate affinity in terms of the Michaelis–Menten kinetics. In this article, we present in silico – in vitro research focused on AQP3, one of the human aquaglyceroporins that is natively expressed in the abundantly available erythrocytes. We conducted 2.1 μs in silico simulations of AQP3 embedded in a model erythrocyte membrane with intracellular–extracellular asymmetries in leaflet lipid compositions and compartment salt ions. From the equilibrium molecular dynamics (MD) simulations, we elucidated the mechanism of glycerol transport at high substrate concentrations. From the steered MD simulations, we computed the Gibbs free-energy profile throughout the AQP3 channel. From the free-energy profile, we quantified the kinetics of glycerol transport that is unsaturated due to glycerol–glycerol interactions mediated by AQP3 resulting in the concerted movement of two glycerol molecules for the transport of one glycerol molecule across the cell membrane. We conducted in vitro experiments on glycerol uptake into human erythrocytes for a wide range of substrate concentrations and various temperatures. The experimental data quantitatively validated our theoretical–computational conclusions on the unsaturated glycerol transport through AQP3 that has high affinity for glycerol.